Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis